Effect of Angelica sinensis polysaccharides on hematopoietic reconstitution in mice after bone marrow transplantation and its mechanism - NIU Xuefang; LIAO Kui; WANG Ziling; HOU Jiying; ZENG Di (陆军军医大学学报, 2022)
Objective To investigate the effect and mechanism of Angelica sinensis polysaccharides (ASP) on the hematopoietic reconstitution of recipient mice after bone marrow transplantation. Methods Bone marrow cells were derived from 10 male C57BL/6J mice (20~25 g), and 30 female recipient mice (8~10 weeks old) were irradiated with 8.0 Gy lethal dose of X-ray. The bone marrow cells from donor mice were infused through tail vein to construct the mouse bone marrow transplantation model. The recipient mice were randomly divided into 3 groups with 10 mice in each group: control group (Ctrl): no bone marrow cells were transplanted in recipient mice; Bone marrow transplantation group (BMT): recipient mice were transplanted with bone marrow cells of donor mice (5×106/each); Bone marrow transplantation+Angelica sinensis polysaccharide group(TASP): radiation dose and the numbers of transplanted bone marrow cells were the same as those of BMT group. At the same time, the recipient mice were given the ASP by intraperitoneal injection (100 mg/kg×9 d). The change in body weight of recipient mice was measured dynamically. In the ninth day after bone marrow cells transplantation, Y chromosome genes in colony-forming cells in spleen and bone marrow cells of recipient mice were detected by PCR. Blood samples were collected from the orbit of the recipient mice to measure the number of WBC, RBC and PLT and the level of HGB. Femurs were taken after the recipient mice were killed, and the number of bone marrow nucleated cells (BMNC) in each femur was counted. The bone marrow cell cycle was detected by flow cytometry. Bone marrow stromal cells (BMSCs) were cultured in vitro. The adherent status of BMSCs was observed, cell proliferative capacity was detected by EDU, and colony forming unit-fibroblastic (CFU-F) numbers were counted. The contents of hematopoietic factors in serum and supernatant of BMSCs were determined by ELISA. Results All mice in the control group died within 7 d, and all animals in the other groups survived. The body weight of mice in the BMT and TASP groups decreased to the lowest level and began to recover after 5~6 d, and the TASP group showed a faster recovery in body weight (P < 0.05). Y chromosome genes were detected in colony-forming cells in spleen and bone marrow cells of recipient mice. The number of WBC, RBC and the level of HGB in the TASP group were increased compared with the BMT group (P < 0.01; P < 0.05). The number of BMNCs in each femur in the TASP group were significantly higher than those in the BMT group (P < 0.05). In the TASP group, the cell proportion decreased in the G0/G1 phase, and the cell proportion in the S and G2/M phase increased compared with the BMT group(P < 0.05); The adherent numbers of BMSCs, proliferation ability and CFU-F numbers in the TASP mice were also significantly higher than those in the BMT group (P < 0.05). The contents of granulocyte-macrophage colony stimulating factor (GM-CSF) and interleukin-3 (IL-3) in serum and GM-CSF and stem cell factor (SCF) in supernatant of BMSCs were increased in the TASP group compared with the BMT group (P < 0.05). Conclusion ASP can promote hematopoietic reconstitution in recipient mice after bone marrow cells transplantation of donor mice, and the preliminary mechanism may be related to improving hematopoietic microenvironment and promoting secretion of hematopoietic factors.